Study on the Apparent Complexities and Challenges behind Supervision and Mentorship in Selected Higher Institutions of Education in South Africa: The Case of Supervisors and Supervisees - Lebaka, Morakeng Edward Kenneth (Selected Topics in Humanities and Social Sciences Vol. 7, 2021)
It is deeply regretted to realize that quite a number of masters and doctoral students divorce academia. The main question the study addressed is: who is the focus of blame? The supervisor or the supervisee or both? Resources indicate that education starts at home and the only habit to form is the habit of forming no habit. The purpose of this study was to investigate the various problems associated with the unpleasant supervisory relationship between the supervisor and the supervisee, and to address these problems with the view to recommending solutions and/or suggestions for a pleasant supervisory relationship. A range of data collection and analysis were employed in this study. A narrative case study design within the qualitative approach was employed/adopted to investigate the problems encountered by supervisors, masters and doctoral students at a purposively selected university. Subjects for this study participated because of their frustration. The sample size of subjects consisted of 10 participants (three supervisors, four masters’ students and three doctoral students) in different stages of their research projects. The use of purposive selection for the interviewees was based on the need to have only participants who have problems with their supervisors, and supervisors who have problems with their supervisees. The interviewees were purposively selected through the assistance of informants. During my association with them, they corroborated my data on their experiences and problems encountered during the supervision process. The primary sources for data collection were informal and unstructured interviews. Secondary sources include books, journals and theses. The results have demonstrated that some supervisors are constructively destructive. They take a responsibility to be a privilege and some students lack commitment, dedication and determination. But when comparing the problems encountered, supervisees seem to encounter more problems as compared to their supervisors. In answering the question: who is the focus of blame? The investigation has shown that both the supervisors and the supervisees are responsible for the unpleasant relationship. In this article, the compatibilities and incompatibilities will be discussed.